Lesions caused by human and domestic and wild animal bites - Haddad Junior, Vidal [UNESP] (FapUNIFESP (SciELO), 2022)
Animal bites are a common problem in the emergency room. There are many reports of isolated cases (mainly of domestic mammals); however, texts with more comprehensive and general guidance on these kinds of bite injuries are necessary, including those caused by wild mammals, reptiles, and even fish. This review aims to update knowledge on this problem, which includes human and domestic and wild animal bites. Health teams in emergency care centers should be aware of the initial and late measures required to control this problem.
Keywords: Animal bite; Bacterial infection; Domestic animal; Fungal infection; Human bite; Wild animal